2004
DOI: 10.1177/0273475304268778
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral Comprehensive Exams in Marketing: Current Practices and Emerging Perspectives

Abstract: Current and emerging issues concerning the written comprehensive exam process are addressed. Both the purpose and structure of this exam are considered. Survey results are presented that describe the purposes of the exam from the perspective of doctoral coordinators. Also included is a description of how marketing departments are currently administering these exams. The movement to nontraditional exam structures is documented, and a description of several of these nontraditional approaches is provided. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 24 publications
(27 reference statements)
5
31
0
Order By: Relevance
“…A factor analysis of individual scale items would be useful in identifying variables that are correlated with one another but independent of other subsets. The independent variable was defined by literature (Fox, 1985;Peterson et al, 1992;Ponder et al, 2004); however, numerous variations were reported in the nontraditional format. This may limit the results found.…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 4 more Smart Citations
“…A factor analysis of individual scale items would be useful in identifying variables that are correlated with one another but independent of other subsets. The independent variable was defined by literature (Fox, 1985;Peterson et al, 1992;Ponder et al, 2004); however, numerous variations were reported in the nontraditional format. This may limit the results found.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…purpose within doctoral counselor education programs and across disciplines (Furstenberg & Nicholas-Casebolt, 2001;Ponder, Beatty, & Foxx, 2004).…”
mentioning
confidence: 99%
See 3 more Smart Citations